Analysis of two-layered film journal bearing with partial slip surface - Rao, T.V.V.L.N. (2014)
Based on the approach of two-layered film consisting of different Newtonian viscosities, the present study examines the effects of partial slip bearing configuration on load capacity and friction coefficient for journal bearing. Navier slip boundary conditions are used to analyze partial slip configuration. A modified Reynolds equation for a journal bearing with two-layered film on a partial slip surface is presented. The modified Reynolds equation is derived taking into consideration of magnitude of lubricant layer's film thickness, viscosities and the extent of partial slip on the bearing surface. The Reynolds boundary conditions are used in the analysis to predict nondimensional load capacity and coefficient of friction. Partial slip of bearing surfaces has a potential to improve load carrying capacity and reduce coefficient of friction for two-layered film journal bearing. Â© (2014) Trans Tech Publications, Switzerland.